2006
DOI: 10.1007/s00455-006-9016-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dysphagia in Acute and Community Mental Health Settings

Abstract: The incidence of dysphagia in the population with mental health disorders may be higher as a result of a number of factors including the nature of the psychiatric disorder, effects of psychiatric medications, co-occurring neurologic conditions, and institutionalization and behavioral changes associated with the mental illness. This study aimed to determine the prevalence of dysphagia among adults with mental health disorders (MHDs) who attend acute and community mental health settings. Sixty attenders at a loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 17 publications
1
58
1
Order By: Relevance
“…study and other published papers are due both to the methods for evaluating swallowing and to observing carefully the relationship between food consistency and clinical signs [5][6][7][8][9][10][11]19,21,[23][24][25] . Therefore, while one of those studies found changes in 30% of subjects, and another found changes in 90% of subjects, we encountered no significant effect of neuroleptic drugs on swallowing 7,11 . As other factors and co-morbidities may cause dysphagia, even in youths, previous reports may have attributed swallowing effects to neuroleptic drugs without first applying appropriate verification methods.…”
Section: Resultsmentioning
confidence: 99%
“…study and other published papers are due both to the methods for evaluating swallowing and to observing carefully the relationship between food consistency and clinical signs [5][6][7][8][9][10][11]19,21,[23][24][25] . Therefore, while one of those studies found changes in 30% of subjects, and another found changes in 90% of subjects, we encountered no significant effect of neuroleptic drugs on swallowing 7,11 . As other factors and co-morbidities may cause dysphagia, even in youths, previous reports may have attributed swallowing effects to neuroleptic drugs without first applying appropriate verification methods.…”
Section: Resultsmentioning
confidence: 99%
“…1 Depression is the most common among these diseases, 2,3 and since mental illness reduces activity in addition to affecting an individual's emotional state, it can lead to diffi culty swallowing in some patients. 4,5 In such cases, it is necessary to administer medicine or nutrition via gavage administration through a gastric or intestinal stoma at the surface of the abdomen, or via a transnasal tube. Recently, the simple suspension method has garnered attention for its effectiveness and for the increased drug stability and safety associated with its use.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of dysphagia is thought to vary according to aetiology and the age of the individual [2]. While dysphagia has been reported to occur in 6% of the general population [4], it is thought to be a more common problem in the population of adults with mental illness [5,6]. Mental disorder or illness is defined as comprising a broad range of problems with different symptoms, generally characterised by some combination of abnormal thoughts, emotions, behaviour, and relationships with others [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some examples are schizophrenia, depression, mental retardation, and disorders due to drug abuse [7]. Possible causes of dysphagia in the population of adults with mental illness include side effects of psychiatric medications, including neuroleptics [5,6,8], behavioural changes associated with the psychiatric disorder itself, concurrent neurological disorders, and the effects of institutionalisation [5,6].…”
Section: Introductionmentioning
confidence: 99%